Aplicação do controle estatístico do processo na análise da qualidade da água da bacia do Rio Mourão - Freitas, Halana Mara Barabacz (2015)
Quality is a primordial demand made by the market for products and services offered by companies. For this they are seeking techniques to allow better control and management of quality of its services. This research arose from the need to control some variables that ensure water quality. The parameters must meet current legislation establishing the procedures and responsibilities relating to the control and surveillance of water quality of water bodies. The work is primarily engaged in applying Statistical Process Control (SPC) in the analysis of water quality in the Mourao River Basin, with the intention of improving the monitoring of these waters. For this, the Shewhart control charts were applied to a control for variables for individual values, type I-MR-S, 9 to physical, chemical and biological parameters that influence the quality of the water in 5 points of Basin. The research is divided into three phases which include: the analysis of the Water Quality Index (AQI), the statistical monitoring with the implementation of the SPC and the finding of socioeconomic factors involved in the quality of this water. The results obtained from use of control charts to monitor this process were similar, with minor changes in water quality. The control charts were developed in free Action 2.6 software. With this study it is concluded that the key monitoring water quality, it passes the limits considered statistically calculated control beyond the limits specified by current legislation. From the statistical control passes to assess process stability. In addition, with the results obtained by the SPC the company responsible for the treatment of municipal water may establish preventive or corrective actions able to improve the process.